Clinical Trials in the Asia-Pacific Region: Challenges and Opportunities - Ambade, Mrunal (IJRDO-Journal of Applied Science, 2018)
The Asia-Pacific (APAC) Region Currently represents some of the fastest growing market for Global Clinical Development activities. The sophisticated healthcare systems, strong and growing infrastructure for quality conduct of clinical research, accessible patient population also there are other numerous factors, such as shortage of trial volunteers in Europe and North America and the availability of highly trained medical professionals in the APAC region, also Asia provides significant opportunities for drug development and marketing makes the APAC region desirable destination for conduction of global clinical trials. However the major challenges in APAC region such as timelines for clinical trials approval, complex and continually evolving regulatory environment, absence of meaningful regulatory harmonization especially with regards to process, requirements and timelines for conduction and approval of clinical trials. This complex regulatory framework can be barrier for other countries, especially those companies that don’t have resource or experience to overcome the obstacles in countries such as China, Japan, Taiwan, Australia, Indonesia , Singapore, Hong Kong , India. In this study we are aiming to understand the clinical trial approval process in APAC Countries and also the reasons for such regulatory challenges